Stress and its relief among undergraduate dental students in Malaysia - Ahmad, M.S.; Yusoff, M.M.M.; Razak, I.A. (SEAMEO Regional Tropical Medicine and Public Health Network, 2011)
This study was conducted to identify the prevalence of stress, types of stressors, consequences of stress and stress relievers among undergraduate dental students at the University of Malaya during the different years of study. A descriptive cross-sectional quantitative study was conducted using a self-administered questionnaire among Bachelor of Dental Surgery students during Years 2 to 5. A 100 response rate was obtained. The instrument asked questions about the preceding academic year. The results of the questionnaire reveal the prevalence of stress was 100. The most common cause of stress among preclinical students was academic concerns and among clinical students was patient management and clinical performance. Physical and behavioral problems were reported as consequences of stress. Most students overcame stress by having strong interpersonal relationships.